1998
DOI: 10.1104/pp.117.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Polygalacturonase Gene Expression in Ripe Melon Fruit Supports a Role for Polygalacturonase in Ripening-Associated Pectin Disassembly

Abstract: Ripening-associated pectin disassembly in melon is characterized by a decrease in molecular mass and an increase in the solubilization of polyuronide, modifications that in other fruit have been attributed to the activity of polygalacturonase (PG). Although it has been reported that PG activity is absent during melon fruit ripening, a mechanism for PG-independent pectin disassembly has not been positively identified. Here we provide evidence that pectin disassembly in melon (Cucumis melo) may be PG mediated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(59 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…Possibly, the conversion of both MeGalUA and MeGlcUA may only be important under certain conditions or at particular developmental stages. This may include conditions that lead to the release or accumulation of GlcUA and GalUA by the assembly/disassembly of pectin and other non-cellulosic polysaccharides (Feingold and Avigad, 1980;Hadfield et al, 1998), and such as occurs during abscission, fruit ripening and softening, pollen grain maturation, and cell expansion. The resolution of these unresolved questions will depend on the characterization of the enzymatic activities and the isolation of the genes involved in the specific conversions.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the conversion of both MeGalUA and MeGlcUA may only be important under certain conditions or at particular developmental stages. This may include conditions that lead to the release or accumulation of GlcUA and GalUA by the assembly/disassembly of pectin and other non-cellulosic polysaccharides (Feingold and Avigad, 1980;Hadfield et al, 1998), and such as occurs during abscission, fruit ripening and softening, pollen grain maturation, and cell expansion. The resolution of these unresolved questions will depend on the characterization of the enzymatic activities and the isolation of the genes involved in the specific conversions.…”
Section: Discussionmentioning
confidence: 99%
“…Polygalacturonase (PG) is the most intensively studied of these cell wall modifying enzymes. The PG belongs to a multi-gene family and various isoforms are expressed in different tissues at different times and in response to different stimuli [47]. However, in spite of their importance, PGs have not been studied yet with QSAR techniques.…”
Section: Qsar Studymentioning
confidence: 99%
“…Previous research on the relationship between light irradiation and fruit ascorbic acid content has shown that ascorbate synthesis and metabolism in fruit are significantly affected by fruit irradiation in addition to leaf irradiation (Gautier et al, 2009). Additionally, the production of pectin and cellulose, which determine fruit hardness, in fruit cells is primarily controlled by the expression of genetic traits (Hadfield et al, 1998;Rose et al, 1997).…”
Section: Discussionmentioning
confidence: 99%